Karakteristik dan Proporsi Percobaan Bunuh Diri pada Siklus Menstruasi - Darma Pratama, Putu Kurnia (E-Jurnal Medika Udayana; Vol 6 No 10 (2017): E-Jurnal Medika Udayana, 2017)
Suicide attempt was higher two to three times in women than men. There have been allegations that the menstrual cycle has a relationship with suicide attempts in women. This study is done to know the proportion of women who attempted suicide at follicular, midcycle, and luteal phase at menstrual cycle and to know the characteristics of suicide attempt women patients based on age, last educational attainment, marital status, and occupation. This study uses cross-sectional descriptive study design. The subjects of this study were women 11 to 50 years old who attempted suicide and comes to Bagian/SMF Psikiatri RSUP Sanglah and met the inclusion criteria. Of the 41 subjects, suicide attempt on follicular phase is 29.2%, on midcycle phase is 9.8%, and on luteal phase is 61%. The study based on the characteristics of subjects gets the result, suicide attempt women patients most commonly at 21-30 years old, had last educational attainment on high school, married, and working. From the result of this study, suicide attempt occur most commonly in women who were at luteal phase of menstrual cycle. With these results, this study expected can be used as a basis for further research that would later be useful in the prevention and control in women who are at risk for suicide attempt.